Biocatalytic Elimination of Pharmaceutics Found in Water With Hierarchical Silica Monoliths in Continuous Flow - Sebai, Wassim; Ahmad, Sher; Belleville, Marie-Pierre,; Boccheciampe, Alexis; Chaurand, Perrine; Levard, Clément; Brun, Nicolas; Galarneau, Anne; Sanchez-Marcano, Jose (Frontiers in Chemical Engineering, 2022)
Pharmaceutical products (PPs) are considered as emerging micropollutans in wastewaters, river and seawaters, and sediments. The biodegradation of PPs, such as ciprofloxacin, amoxicillin, sulfamethoxazole, and tetracycline by enzymes in aqueous solution was investigated. Laccase from Trametes versicolor was immobilized on silica monoliths with hierarchical meso-/macropores. Different methods of enzyme immobilization were experienced. The most efficient process was the enzyme covalent bonding through glutaraldehyde coupling on amino-grafted silica monoliths. Silica monoliths with different macropore and mesopore diameters were studied. The best support was the monolith featuring the largest macropore diameter (20 µm) leading to the highest permeability and the lowest pressure drop and the largest mesopore diameter (20 nm) ensuring high enzyme accessibility. The optimized enzymatic reactor (150 mg) was used for the degradation of a PP mixture (20 ppm each in 30 ml) in a continuous recycling configuration at a flow rate of 1 ml/min. The PP elimination efficiency after 24 h was as high as 100% for amoxicillin, 60% for sulfamethoxazole, 55% for tetracycline, and 30% for ciprofloxacin.